2008
DOI: 10.1088/0029-5515/48/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Off-axis current drive and real-time control of current profile in JT-60U

Abstract: Aiming at optimization of current profile in high-β plasmas for higher confinement and stability, a real-time control system of the minimum of the safety factor (q min) using the off-axis current drive has been developed. The off-axis current drive can raise the safety factor in the centre and help to avoid instability that limits the performance of the plasma. The system controls the injection power of lower-hybrid waves, and hence its off-axis driven current in order to control q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…Analysis of far off-axis CD in JT-60U [27], presented in the right part of Fig. 6, clearly showed that current can be driven as far off-axis as ρ=0.8, but again the profile of the driven current was not consistent with the theoretical prediction that in this case showed more inward shifted profiles.…”
Section: Conventional Heating and Current Drive Scenariosmentioning
confidence: 76%
“…Analysis of far off-axis CD in JT-60U [27], presented in the right part of Fig. 6, clearly showed that current can be driven as far off-axis as ρ=0.8, but again the profile of the driven current was not consistent with the theoretical prediction that in this case showed more inward shifted profiles.…”
Section: Conventional Heating and Current Drive Scenariosmentioning
confidence: 76%
“…Other authors stress that the Kubo number (ratio of decorrelation time to fast-ion time of flight) is a crucial parameter and that phase averaging may not occur at all [5]. A compilation of data [6] in the large energy regime (E=T ) 10) confirms the conventional wisdom, but some anomalies at smaller E=T have been reported [7,8].…”
mentioning
confidence: 85%
“…In most of these experiments the beam driven current was located on-axis, including those with N-NBI [16,17]. The only off-axis current drive experiments (with 2 MW NBI power) -apart from ASDEX Upgrade -have been reported by JT-60U [15,19].…”
Section: Current Profile Modification By Off-axis Nbi On Asdex Upgradementioning
confidence: 99%